Formulation and Physical Evaluation of Ointment Containing Ageratum conyzoides L. Leaf Extract as a Herbal Medicine - Mailani, Senfia Liberti; Sulastri, Titin; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
Babadotan leaves (Ageratum conyzoides L.) are a plant that has long been used in traditional medicine due to their anti-inflammatory, antibacterial, and wound healing properties. This study aims to formulate and evaluate ointment preparations containing babadotan leaf extract as a herbal medicine. This study used a descriptive method in the laboratory and described the tests obtained. The extract was obtained through maceration using 96% ethanol solvent. Formulation evaluation included organoleptic tests, homogeneity, pH, spreadability, adhesiveness, and viscosity. The results showed that formulations F1, F2, and F3 were yellowish green with a distinctive smell of babadotan leaves and were solid because they contained thick babadotan leaf extract. All ointment formulations had homogeneous properties, indicated by the absence of coarse grains in the ointment. The spreadability of formulas F2 and F3 met the criteria, while F1's spreadability was slightly below the lower limit. All three formulas had higher adhesiveness than the standard. The pH values of F2 and F3 were within normal limits and safe to use, while F1 was slightly more alkaline but still acceptable for topical use. All formulas were within the appropriate range for ointments, namely 2,000–50,000 cp. In conclusion, the ointment formulation based on babadotan leaf extract has the potential to be an effective herbal remedy and can be further developed in the pharmaceutical field.